Novelties in Brazilian Stachytarpheta (Verbenaceae): A new species and taxonomic updates - Cardoso, Pedro Henrique; Neto, Luiz Menini; Salimena, Fátima Regina Gonçalves; Trovó, Marcelo (Phytotaxa, 2020)
As part of our ongoing studies on the Brazilian Stachytarpheta (Verbenaceae), we describe Stachytarpheta oblongifolia P.H.Cardoso & Salimena from Central Brazil, propose the new combination Stachytarpheta chascanoides (Moldenke) P.H.Cardoso, and reestablish Stachytarpheta mollis Moldenke. In addition, several taxa are here treated differently from previous classifications, namely Stachytarpheta atriflora S.Atkins is synonymized with Stachytarpheta glauca (Pohl) Walp.; Stachytarpheta caatingensis S.Atkins and Stachytarpheta villosa var. bahiensis Moldenke are synonymized with Stachytarpheta brasiliensis Moldenke; Stachytarpheta canescens var. elliptica Moldenke is synonymized with Stachytarpheta hirsutissima Link; Stachytarpheta gesnerioides var. simplex (Hayek) Moldenke is synonymized with Stachytarpheta gesnerioides Cham. var. gesnerioides; Stachytarpheta galactea S.Atkins is synonymized with Stachytarpheta coccinea Schauer; and, Stachytarpheta spathulata Moldenke subsp. spathulata and Stachytarpheta spathulata subsp. mogolensis S.Atkins are synonymized with Stachytarpheta chascanoides. Lectotypes are designated for 11 names, Stachytarpheta gesnerioides var. simplex, Stachytarpheta glauca, Stachytarpheta hatschbachii Moldenke, Stachytarpheta integrifolia (Pohl) Walp., Stachytarpheta longispicata (Pohl) S.Atkins subsp. longispicata, Stachytarpheta longispicata subsp. brevibracteata (Moldenke) S.Atkins, Stachytarpheta longispicata var. parvifolia (Moldenke) S.Atkins, Stachytarpheta lythrophylla Schauer, Stachytarpheta martiana Schauer, Stachytarpheta obovata Hayek, and Stachytarpheta speciosa Pohl ex Schauer.